Tropical town and other poems - Selva, Salomón de la, 1893-1959 (Recovering the U.S. Hispanic Literary Heritage Project publication., 1999)
Poems by a late Nicaraguan writer. In A Prayer for the United States, he wrote: "Apocalyptic blasts are ravaging over-sea. / With lure of flag and conquest the harlot War is wooing. / The horse John saw in Patmos its dread course is pursuing. / I pray the Lord He shelter the stars that shelter me."